2013
DOI: 10.1002/kin.20751
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Brønsted and Hammett Correlations Associated with Reactions of 4‐Chloro‐7‐nitrobenzofurazan with Anilines in Dimethyl Sulfoxide Solution

Abstract: The kinetics and mechanism of nucleophilic aromatic substitution reactions of 4-chloro-7-nitrobenzofurazan 1 with 4-X-substituted anilines 2a-g (X = OH, OCH 3 , CH 3 , H, I, Cl, and CN) are investigated in a dimethyl sulfoxide (Me 2 SO) solution at 25 • C. The Hammett plot of log k 1 versus σ is nonlinear for all the anilines studied due to positive deviations of the electron-donating substituents. However, the corresponding Yukawa-Tsuno plot resulted in a good linear correlation with σ + r (σ + − σ ). The cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 38 publications
(36 reference statements)
5
15
0
Order By: Relevance
“…This shows that the reactions are highly sensitive to the basicity of the amines used irrespective of the steric hindrances of the substituents on the amine moiety. Similar observations were made by Goumont et al and Um et al in the reactions of anilines with 4‐chloro‐7‐nitrobenzofuran and pyridinolysis of O ‐4‐nitrophenyl benzoates and thionobenzoates. The p K a values of the amines in water with R = H (9.34), methyl (9.58), and ethyl (9.68) substituents are from .…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…This shows that the reactions are highly sensitive to the basicity of the amines used irrespective of the steric hindrances of the substituents on the amine moiety. Similar observations were made by Goumont et al and Um et al in the reactions of anilines with 4‐chloro‐7‐nitrobenzofuran and pyridinolysis of O ‐4‐nitrophenyl benzoates and thionobenzoates. The p K a values of the amines in water with R = H (9.34), methyl (9.58), and ethyl (9.68) substituents are from .…”
Section: Resultssupporting
confidence: 87%
“…A plot of log k versus pK a values of amines again showed a linear correlation ( Fig. 4) with two different straight lines with β values of 3.68 and −9.74 for electron-withdrawing substituents and [15,20] in the reactions of anilines with 4-chloro-7-nitrobenzofuran and pyridinolysis of O-4-nitrophenyl benzoates and thionobenzoates. The pK a values of the amines in water with R = H (9.34), methyl (9.58), and ethyl (9.68) substituents are from [28].…”
Section: Brønsted Correlationmentioning
confidence: 82%
See 1 more Smart Citation
“…Careful examination of the literature has shown that Brönsted‐type plots with slopes β nuc > 1 are rarely observed in σ‐complexation reactions. However, β nuc values close to or greater than 1 have been reported in the literature for nucleophilic aromatic substitutions reactions, for example, β nuc = 1.24 for reaction of N1‐methyl‐4‐nitro‐2,1,3 benzothiadiazolium tetrafluoroborate with a series of 4‐X‐substituted anilines (X = OH, OMe, Me, and H) in acetonitrile at 20°C, and β nuc = 1.60 for reactions of 4‐chloro‐7‐nitrobenzofurazan with 4‐X‐substituted anilines (X = OH, OMe, Me, H) in dimethyl sulfoxide solution at 25°C . In this regard, it is interesting to note that unusual high Brønsted β nuc value of 1.22 has also been reported by El‐Bardan in the reaction of phenoxide anions with 2‐chloro‐5‐nitropyridine in methanol …”
Section: Resultsmentioning
confidence: 83%
“…That this value is higher than those, 0.5-0.7, normally associated [2] with nucleophilic substitutions may beattributed to the strongly electron-withdrawing effect of the trinitrobenzene ring. Values of β close to or higher than one have been attributed to the intervention of an SET pathway [21,22] for substitution but there is no evidence that this applies here. Phenols were the purest available commercial specimens.…”
Section: Kinetic Analysismentioning
confidence: 70%